Construction of a predictive model of abdominal lymph node metastasis in thoracic esophageal squamous cell carcinoma and preliminary analysis of its effect on target for postoperative radiotherapy - Gao, Hong-Mei; Zhang, Xue-Yuan; Shen, Wen-Bin; Xu, Jin-Rui; Li, You-Mei; Li, Shu-Guang; Zhu, Shu-Chai (Frontiers in Surgery, 2022)
Purpose :To investigate the influencing factors of abdominal lymph node metastasis in thoracic esophageal squamous cell carcinoma (TESCC), and to construct its predictive model, in order to analyze the targets for postoperative radiotherapy. Methods and materials:From January 2008 to December 2014, the clinicopathological data of 479 patients who underwent radical resection for esophageal cancer in the Fourth Hospital of Hebei Medical University were collected and retrospectively analyzed. The influencing factors of postoperative abdominal lymph node metastasis were analyzed, and a predictive model was constructed based on their independent influencing factors. Receiver operating characteristic (ROC) curve was utilized to analyze the predictive value of this model; in the meantime, the postoperative locoregional recurrence (LRR) of this group was analyzed. Results:The postoperative pathology of all patients showed that the lymph node metastasis rate (LNR) was 39.7%, of which the abdominal lymph node metastasis rate was 22.0%. Logistic regression analysis revealed that the patient's lesion location, pN stage, vascular invasion, LND and mediastinal lymph node metastasis were independent risk factors for the positive rate of abdominal lymph nodes after surgery (P=0.000, 0.000, 0.033, 0.000, 0.000). The probability of abdominal lymph node metastasis was Y=ex/(1+ex), and X=-5.502+1.569×lesion location+4.269×pN stage+1.890×vascular invasion+1.950×LND-4.248×mediastinal lymph node metastasis. The area under the ROC curve (AUC) of this model in predicting abdominal lymph node metastasis was 0.962 (95%CI: 0.946-0.977). This mathematical model had a high predictive value for the occurrence of abdominal lymph node metastasis (P=0.000), and the sensitivity and specificity of prediction were 94.6% and 88.3% respectively. The overall survival rate was significantly higher (X2=29.178, P=0.000), while abdominal lymph node recurrence rate was lower in patients with negative abdominal lymph nodes than in those with negative lymph nodes (1.4%&7.7%, X2=12.254, P=0.000). Conclusion:The lesion location, pN stage, vascular invasion, LND and mediastinal lymph node metastasis are independent influencing factors of abdominal lymph node metastasis in patients with TESCC. The mathematical model constructed by these indicators can accurately predict abdominal lymph node metastasis, which can help clinicians to choose the targets for postoperative radiotherapy.